TACHY-DEPENDENT DISPERSION OF QT INTERVAL AND INTRAVENTRICULAR CONDUCTIVITY DISTURBANCES: CLINICOINSTRUMENTAL PARALLELS - Yu. N. Fedulaev; O. S. Fedoseeva; G. A. Khayretdinova; O. V. Reyner (Российский кардиологический журнал)
In 28 patients with intraventricular block and coronary heart disease (CHD), as well as in 20 professional ex-athletes with impaired intraventricular conductivity, corrected QT interval dispersion at maximal and minimal heart rate (HR) was assessed, based on the Holter ECG monitoring data. In both groups, absolute and corrected QT interval dispersion at minimal HR was similar and within minimally pathological range. For maximal HR, absolute and corrected QT interval dispersion increased by 21,3%, comparing to baseline, and reached moderately pathological range in CHD patients. In the other group, absolute and corrected QT interval dispersion decreased by 22,6%, compared to baseline, and reached non-pathological range.